The importance of understanding perceptions of accessibility when addressing transport equity: A case study in Greater Nottingham, UK - Angela Curl (Journal of Transport and Land Use)
To deal with issues of equity in transport, increasing attention is being paid to addressing inequalities in accessibility. Existing approaches to measuring accessibility tend to focus on objective measurement, often using journey time as an indicator of spatial separation of people from places. However, using objective measures of spatial accessibility could obscure inequities in accessibility that occur due to differences in perceptions of accessibility among (groups of) individuals.